Leg exercises with a serrated rubber ball and virgin coconut oil can increase the skin moisture of the feet of Diabetes Mellitus patients - I Wayan Sukawana; Ni Made Wedri; Ni Komang Ayu Indriyani; I Made Sukarja (Nursing and Health Sciences Journal (NHSJ), 2025)
Chronic hyperglycemia in patients with Diabetes Mellitus can cause autonomic neuropathy, resulting in decreased skin moisture in the feet. This study aims to test the impact of foot exercises with a serrated rubber ball and Virgin Coconut Oil (VCO) on skin moisture in patients with Diabetes Mellitus. This study was a pre-experimental design with a sample of 19 respondents of type 2 Diabetes Mellitus patients, who were taken randomly. Skin moisture data for the feet were measured using a digital skin tester one day before and after treatment. Foot exercises with a serrated rubber ball and VCO were carried out every two days for 30 minutes within 3 weeks. The average skin moisture of the feet before treatment was 17.80% ± 3.62%, and after treatment, 26.46 ± 6.34%%. The results of the Paired Sample T-Test showed a significant effect of the combination of foot exercises with a serrated rubber ball and VCO on increasing the skin moisture of the feet of patients with Diabetes Mellitus (p-value = 0.00). Thus, applying foot exercises with a serrated rubber ball and VCO effectively increases the skin moisture of the feet of patients with Diabetes Mellitus.